Things - Brown, Bill (Chicago The University of Chicago Press, 2004)
This book is an invitation to think about why children chew pencils; why we talk to our cars, our refrigerators, our computers; rosary beads and worry beads; Cuban cigars; why we no longer wear hats that we can tip to one another and why we don't seem to long to; what has been described as bourgeois longing. It is an invitation to think about the fetishism of daily life in different times and in different cultures. It is an invitation to rethink several topics of critical inquirycamp, collage, primitivism, consumer culture, museum culture, the aesthetic object, still life, "things as they are," Renaissance wonders, "the thing itself"within the rubric of "things," not in an effort to foreclose the question of what sort of things these seem to be, but rather to suggest new questions about how objects produce subjects, about the phenomenology of the material everyday, about the secret life of things.Based on an award-winning special issue of the journal Critical Inquiry, Things features eighteen thought-evoking essays by contributors including Bill Brown, Matthew L. Jones, Bruno Latour, W. J. T. Mitchell, Jessica Riskin, Jeffrey T. Schnapp, Peter Schwenger, Charity Scribner, and Alan Trachtenberg.